Fenologia, produção e pós-colheita de figueira cv. Roxo de Valinhos no Oeste Potiguar - Silva, Francisco Sidene Oliveira (2016)
The culture of fig (Ficus carica L.) constitutes one of the most important fruit crops, raising Brazil to the status of tenth largest producer of figs in the world. The fig 'Roxo de Valinhos' highly perishable and sensitive handling product. However, studies of phenology, production and post-harvest quality of the fruit of fig, especially in semi-arid regions are still rare. This aimed to evaluate the phenology, the productive aspects, post-harvest and storage time of fig cv. Purple of Valinhos in Natal west. The experiment was conducted at two different times, where post-harvest occurred in November 2014, and phenology in the period from July to December 2015. For the characteristics of phenology, we used descriptive statistics, while for the characteristics quantitative and qualitative, we used regression and mean test by Tukey test at 5% probability. For post-harvest, we used a completely randomized design in a 5x3 factorial scheme, where 5 is the storage periods (0, 4, 8, 12 and 16 days) and 3 is maturity stages (50, 75 and 100%), with 4 repetitions and 40 fruits per maturity stage. The fruits were harvested and taken to the Postharvest the Federal Rural University of the Semi-Arid Laboratory (UFERSA), and were stored in a cold room (10 ± 2 ° C and 80-90% RH) for a period of 16 days, being evaluated every 4 days. The fig tree cultivation showed good adaptability and precocity to the semi-arid region in all phenological phases compared with temperate regions. In terms of the fruit quality, the fig tree shows a promising fruit for cultivation in semi-arid region